Association of subjective olfactory dysfunction and 12‐item odor identification testing in ambulatory COVID‐19 patients. Issue 11 (10th September 2020) - Prajapati, Divya P.; Shahrvini, Bita; MacDonald, Bridget V.; Crawford, Kayva L.; Lechner, Matt; DeConde, Adam S.; Yan, Carol H.
Abstract : Background: Acute loss of smell and taste are well‐recognized symptoms of coronavirus disease 2019 (COVID‐19), yet the correlation between self‐reported and psychophysical olfactory function remains unclear. Understanding the reliability of self‐reported smell loss in ambulatory cases can assess the utility of this screening measure. Methods: A prospective, longitudinal study evaluating patient‐reported and measured olfactory function using the validated 12‐item Brief Smell Identification Test (BSIT) was conducted on adult outpatients with COVID‐19. Patient‐reported olfaction scores using a visual analog scale (VAS) were obtained at baseline, time of COVID‐19 testing, and time of BSIT completion. Linear associations between VAS and BSIT were evaluated using Spearman's correlation coefficient and the sensitivity, specificity, and accuracy of VAS scores were calculated. Logistic regression identified characteristics associated with accurate assessment of olfactory function. Results: A total of 81 polymerase chain reaction (PCR)‐confirmed COVID‐19 positive subjects, of whom 54 self‐reported smell loss, were prospectively recruited ≤5 days from diagnosis date between May 8, 2020, and July 8, 2020. Self‐reported smell loss had good discriminative ability in identifying abnormal BSIT (area under receiver operating curve [AUC] 0.82, 95% confidence interval [CI], 0.71 to 0.92). A VAS <5 demonstrated sensitivity of 0.62 and specificity of 0.94 for predicting hyposmia (BSIT ≤8) with accuracy of 82.7%, whereas a VAS <9 had highest sensitivity at 0.86. Moderate bivariate linear associations were found between VAS and BSIT scores ( r s = 0.59, p < 0.001). Conclusion: Self‐reported olfactory loss associated with COVID‐19 has a strong ability to predict abnormal olfactory function though the 2 measures are moderately correlated. Subjective olfactory assessment is useful in screening olfactory dysfunction at early disease time points when psychophysical testing cannot be conducted.